2011
DOI: 10.2478/v10245-011-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light colour on forced hyacinth

Abstract: Three cultivars of Hyacinthus orientalis L. were forced under artificial light using fluorescent lamps emitting white, blue, green, yellow and red light. Quantum irradiance was determined as 12.5 and 25 µmol m-2 s-1. Day length was 12 and six hours, respectively. Daily light integral was 0.54 mol m-2. A significant effect of light colour on flowering date and plant quality was observed. Plants forced in blue and red light were the first to flower. Plants exposed to red light formed longer inflorescences. Plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…'Fondant', this elongation caused maximal flabbiness of inflorescence shoots and leaves. Other experiments by m i g i e l s k a and J e r z y [13] revealed that hyacinths flower earliest under blue and red fluorescent light. Plants forced under lamps emitting red light form longer inflorescences and are flabbier.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…'Fondant', this elongation caused maximal flabbiness of inflorescence shoots and leaves. Other experiments by m i g i e l s k a and J e r z y [13] revealed that hyacinths flower earliest under blue and red fluorescent light. Plants forced under lamps emitting red light form longer inflorescences and are flabbier.…”
Section: Introductionmentioning
confidence: 89%
“…Little is known about the possibility of forcing hyacinths under artificial light [10,11,12,13]. Based on the research conducted by m i g i e l s k a and J e r z y [12], it is apparent that post-harvest longevity of hyacinths depends on, among other things, the length of the flowering period, which in turn is the longest after the application of white and blue light.…”
Section: Introductionmentioning
confidence: 99%